Are digital picturings representations? - Webmoor, T; Carusi, A; Novakovic, G (2010)
The philosopher of art Roger Scruton has claimed that photographic images are not representations, on the basis of the role of causal rather than intentional processes in arriving at the content of a photographic image (Scruton, 1981). His claim was controversial at the time, and still is, but had the merit of being a springboard for asking important questions about what kinds of representation result from the technologies used in depicting and visualising. In the context of computational picturing of different kinds, in imaging and other forms of visualisation, the question arises again, but this time in an even more interesting form, since these techniques are often hybrids of different principles and techniques. A digital image results from a complex interrelationship of physical, mathematical and technological principles, embedded within human and social situations. This paper consists of three sections, each presenting a view of the question whether digital imaging and digital visual artefacts generally are representations, from a different perspective. These perspectives are not representative, but aim only to accomplish what Scruton’s paper did succeed in accomplishing, that is, being a provocation and a springboard for a broader discussion.